EU policies and strategies and territorial cohesion - Medeiros, E.; Caramelo, S. (Public policies for territorial cohesion, 2023)
Territorial cohesion is an EU concept and, in recent decades, several EU policies, such as the EU Cohesion Policy, have contributed decisively to promoting territorial development in socioeconomically lagging EU regions. It resembles a European political ideal that collectively we try to achieve, but without knowing very well what it is. However, as several studies have concluded, although at the EU level certain territorial cohesion trends have been attained in some policy arenas, at the national level there is no clear evidence that EU policies have contributed to achieving territorial cohesion trends in recent decades in EU member states. In this context, this chapter critically discusses the evolution of EU policies and strategies to promote territorial cohesion in the EU territory since the implementation of the EU Cohesion Policy (1989). Crucially, it presents a critical overview of policy rationales presented by EU development agendas (e.g. Lisbon, Europe 2020, etc.), the European Spatial Development Perspective, the Green Paper for Territorial Cohesion, as well as the three EU territorial agendas. It concludes that territorial cohesion has never been at the core of EU mainstream development agendas and that the territorial agendas have not yet contributed to inverting this panorama. It also concludes that EU Cohesion Policy, with the exception of the current programming period (2021–27) has never included all the crucial dimensions of territorial cohesion in its main strategic objectives: socioeconomic cohesion + environmental sustainability + territorial cooperation/governance + morphologic polycentricity.